The Use of van Dijk’s Ideological Square in The Construction of In-Group and Out-Group Dichotomy in Dunya Mikhail’s Poetry - Hamadneh, Tarik; Abdul Muttaleb, Fuad (International Journal of Language and Literary Studies, 2025)
This study applies van Dijk's ideological square model to the war poetry of the Iraqi poetess Dunya Mikhail to identify the discursive strategies that construct an in-group/out-group dichotomy and represent the multifaceted impacts of war on Iraqi society. A qualitative analysis of sixteen purposively selected poems was conducted, focusing on the four mechanisms of the ideological square: emphasising positive self-representation and negative other-representation while de-emphasising their opposites. The analysis reveals Mikhail's consistent deployment of these strategies, augmented by rhetorical devices such as stark imagery and ironic personification. This approach vividly portrays civilian estrangement and the devastation of war, creating a discourse that scrutinizes the ideologies of war perpetrators. Mikhail’s poetry offers a compelling counter-narrative that not only documents civilian suffering but also serves as a critical tool for challenging dominant conflict narratives. The study concludes that Mikhail has succeeded in systematically employing the model’s four strategies of emphasising “our” good and “their” bad, while deemphasising “our” bad and “their” good—to construct a powerful artistic expression and moral critique.